EOCENE-OLIGOCENE CLIMATE BASED ON PALYNOLOGICAL RECORDS - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2006)
This study is a part of the investigation on Tertiary paleoclimate conducted by LEMIGAS Stratigraphy Group. The paleoclimate reconstruction covers most area of western Indonesia including South Sumatra Basin, Sunda-Asri Basin, Northeast Java Basin South Kalimantan and Northeast Java Basin, West Natuna and South Sulawesi (Figure 1). This paper is aimed to figure out the regional paleoclimate of western Indonesia which occurred during Eocene-Oligocene. In fact, the knowledge of paleoclimate is useful to define sea level changes which are believed to have relationship with stratigraphy and sedimentology of these areas. The paleoclimate interpretation can be approached using different tools such as biostratigraphy and geochemistry. In this study, paleoclimate is interpretated based on biostratigraphy (microfossil evidences) including palynomorph and foraminifer. Palynomorphs were mainly applied on the non-marine to transitional sections, whilst foraminifers were used in interpreting shallow to deep marine sediments. In fact, most interpretations rely on palynological evidences as these simply provide suitable data for paleoclimate analysis. In case of both microfossils appear in the same section, the paleoclimate interpretation based on palynomorph can be placed in a certain stratigraphic level which is defined based on the occurrence of the age-restricted foraminifer. The paleoclimate interpretation of certain strati- graphic level is based on the compilation of palynological and foraminiferal data deriving from different areas. This method is used to obtain representative picture of paleoclimate which occurs in the selected stratigraphic range of the western Indonesia